$$f(a + x) = \sum_{k=0}^∞ \frac{f^{(k)}(a) x^k}{k!}$$(adsbygoogle = window.adsbygoogle || []).push({});

Usually written as:

$$f(t) = \sum_{k=0}^∞ \frac{f^{(k)}(a) (t-a)^k}{k!}$$

Where ##t = a + x##

Is the taylor expansion supposed to give the same result for all ##a##? The reason this confuses me is because this seems to suggest that ##f(1 + x) = f(4 + x) = f(π + x)## and so on, which is usually not the case. Where did I go wrong?

**Physics Forums | Science Articles, Homework Help, Discussion**

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Help with Taylor Series

Loading...

**Physics Forums | Science Articles, Homework Help, Discussion**